KUALITAS SISTEM INFORMASI, KUALITAS INFORMASI, DAN PERCEIVED USEFULNESS TERHADAP KEBERHASILAN IMPLEMENTASI SOFTWARE AKUNTANSI - AGUSTINES TANANJAYA, VENIA (Berkala Ilmiah Mahasiswa Akuntansi)
Accounting software implementation process means how an accounting software to facilitate the performance of the user to produce a quality information and helps users of information in decision making. Companies can measure the success of the software implementation of accounting with respect to the quality of information systems, information quality, and perceived usefulness are strongly associated with users of accounting software. The process of implementation of good accounting software will help the company achieve its business objectives.